Multilevel amplitude and phase regeneration in a nonlinear amplifying loop mirror with a phase-sensitive amplifier - Röthlingshöfer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Transparent Optical Networks (ICTON), 2012)
A novel regenerator scheme for all-optical multilevel simultaneous amplitude and phase noise suppression is proposed. For a star-8QAM signal, consisting of two amplitude and four phase states, EVM reduction is 4 dB and 2.5 dB for the high- and low-power states, respectively. The limiting effects of the regenerator performance have been considered.
lhft_intern.bib::Roethlingshoefer2012cb